Is Virtual-Physical or Physical-Virtual Manipulatives in Physics Irrelevant within Studio Physics Environment? - Jean-Pierre Atanas (Athens Institute for Education and Research, 2018)
The purpose of this study is to explore factors that affect exclusively physical, virtual and both a Virtual-Physical (VP) and Physical-Virtual (PV) sequence of manipulatives within Studio Physics environment. In this environment students actively work together to learn through real world experimentation and simulation based activities. Activities and tests have been especially designed for that purpose. Students, from different sections and for two consecutive academic years, have been involved in the study. Statistics show that comprehensive learning groups (i.e. any combination of PV or VP sequence) performed better than any other setting. The study also pinpoints the importance of the sequence for which virtual or physical experiments of some specific concepts are initially introduced to students.